PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 8 DURI BARAT KECAMATAN MANDAU KABUPATEN BENGKALIS - Fithri, Shafwani; Alpusari, Mahmud; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research was carried out because of low learning value of fifth grader students in Science subject of SD Negeri 8 Duri Barat District of Mandau Kabupaten Bengkalis . Among 20 Students, 7 students (35%) reached the standard of completeness while the students could not reach the standard is 13 students ( 35%) with average 58,5. The purpose of this study is to increase the fifth grader students’ value in Science subject of SD Negeri 8 Duri Barat Kabupaten Bengkalis with the application of Problem Based Learning. The results obtained by the average value of the basic score of 58.5 in the first cycle increased by 10.5% to 69. In the second cycle the average value of students also increased as much as 23.25% to 92.25. On the basis of completeness score of Science, student learning outcomes is only 35% (not complete). After the teacher was applying the Problem Based Learning in the first cycle the classical completeness increase becoming 50 % ( not complete), In the second cycle the classical completeness also increased becoming 95%. Teacher’s activity at the first meeting is 60% in enough category level. The second meeting increased becoming 75% in good category level. In the second cycle increased up to 85% in very good category level. In the second meeting of second cycle, the student’s activity increased becoming 100% in the very good category level. The students’ activity in the cycle I of first meeting got 55% percentage in enough category level. The second meeting of the first cycle to 65% in good category. At the first meeting of the second cycle of student activity increased to 75% in good category, and the second meeting of the second cycle increased again to 100% with a very good category.Key words : Problem Based learning, the Science’s result study